Epidendrum dayseae, a new species of Orchidaceae (Laeliinae) from northern Brazil - Krahl, Amauri H.; Cordeiro, Joel M. P.; Hagsater, Eric (Phytotaxa, 2022)
A new Epidendrum species of the Nocturnum group is proposed for the Brazilian central Amazon, near Manaus. It is described, illustrated, and compared with similar species. Epidendrum dayseae can be recognized by the pendent stem, the long, narrow leaves, a relatively long floral pedicel, and the lateral lobes of the lip smaller than the mid-lobe and deeply separated. The new species resembles E. longicolle, but is distinguished by the union between of the lateral and mid-lobes of the lip being under half the mid-lobe length. The new species is also compared with E. plurifolionocturnum. Its chromosome number is 2n = 4x = 80, with a band pattern similar to other species of the Nocturnum group.